Preparation of ultrabright AIE nanoprobes via dynamic bonds. Issue 46 (18th November 2015) - Wan, Qing; He, Chengbin; Wang, Ke; Liu, Meiying; Huang, Hongye; Huang, Qiang; Deng, Fengjie; Zhang, Xiaoyong; Wei, Yen
Abstract: Preparation and biomedical applications of aggregation induced emission (AIE) dye based fluorescent nanoprobes (FNPs) have been extensively investigated in recent years. And great efforts have been devoted toward fabrication of AIE dye based FNPs through both noncovalent and covalent strategies. However, to the best of our knowledge, the preparation of AIE dye based FNPs via dynamic bonds is rarely reported. In this work, ultrabright FNPs based on AIE dyes have been fabricated using aldehyde-terminated polyethylene glycol (CHO-PEG-CHO) with molecular weight of 2000 Da and 2, 2′-diaminotetraphenyl ethylene (TPE-NH2 ) through formation of Schiff base. The resulting TPE contained copolymers are prone to self-assemble into stabilized core shell nanoparticles (TPE@PEG FNPs). The successful formation of TPE@PEG FNPs was confirmed by 1 H nuclear magnetic resonance spectroscopy, transmission electron microscopy, fluorescence spectroscopy and Fourier transform infrared spectroscopy. Due to their amphipihlic properties, TPE@PEG FNPs displayed high water dispersibility and strong fluorescence intensity. Furthermore, biological evaluation results demonstrated that TPE@PEG FNPs possess excellent biocompatibility and can be facilely internalized by cells. The extraordinary fluorescent properties, excellent water dispersibility as well as the desirable biocompatibility make TPE@PEG FNPs promising candidates for biomedical applications. On the other hand, because of the pH stimuli responsiveness of Schiff base, TPE@PEG FNPs are expected to exhibit some advantages for biomedical applications as compared with the FNPs fabricated by noncovalent and covalent strategies. Graphical abstract: This work reported the fabrication of AIE dye based fluorescent nanoprobes through formation of dynamic bonds, which should be very useful for development of stimuli responsive nanotheranostics.